2017
DOI: 10.1002/jcb.26257
|View full text |Cite
|
Sign up to set email alerts
|

Pathological role of a point mutation (T315I) in BCR‐ABL1 protein—A computational insight

Abstract: BCR-ABL protein is one of the most potent target to treat chronic myeloid leukemia (CML). Apart from other mutations, T315I is especially challenging as it confers resistance to all first-and second-generation tyrosine kinase inhibitors. So, a thorough study of altered behavior upon mutation is crucially needed. To understand the resistance mechanism of mutant BCR-ABL protein, we organized a long-term molecular dynamics simulation (500 ns) and performed the detailed comparative conformational analysis. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 34 publications
(70 reference statements)
0
84
0
Order By: Relevance
“…The produced trajectories of MD simulations were then used to generate the root mean square deviation (RMSD) and hydrogen bond graphs by various inbuilt scripts of GROMACS. MD simulations were used in several integrative studies to tackle various conditions such as cancers , identification of novel inhibitors Sadhasivam & Vetrivel, 2019;Sharma et al, 2020;Singh et al, 2019), role of various mutations (Nagarajan et al, 2020;Rajendran et al, 2018), and exploration of drug resistance mechanisms (Rajendran & Sethumadhavan, 2014).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The produced trajectories of MD simulations were then used to generate the root mean square deviation (RMSD) and hydrogen bond graphs by various inbuilt scripts of GROMACS. MD simulations were used in several integrative studies to tackle various conditions such as cancers , identification of novel inhibitors Sadhasivam & Vetrivel, 2019;Sharma et al, 2020;Singh et al, 2019), role of various mutations (Nagarajan et al, 2020;Rajendran et al, 2018), and exploration of drug resistance mechanisms (Rajendran & Sethumadhavan, 2014).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Owing to the application of a high-through sequencing method, the identification of disease-related biomarkers is effectually stated in many research articles. [14][15][16][17][18][19][20] Gene expression profiling has been used to find various differentially expressed genes (DEGs), and DNA methylome analysis has made it possible to identify differentially methylated genes (DMGs). Although multiple studies have demonstrated specific genes with aberrant DNA hypermethylation or hypomethylation in THCA, 21,22 the comprehensive profile and pathways of the interaction network remain elusive.…”
mentioning
confidence: 99%
“…25 The unfolding of proteins leads to the loss of secondary structure which reduces the stability of the molecule. 27 Therefore, secondary structures of homodimeric gramicidin peptides were interpreted using Visual Molecular Dynamics (VMD) program. 27 Therefore, secondary structures of homodimeric gramicidin peptides were interpreted using Visual Molecular Dynamics (VMD) program.…”
Section: Secondary Structure Profilementioning
confidence: 99%
“…Thus, g-A exhibited high compactness in packing of atoms, which leads to enhanced its structural stability. 27,50 RMSD for g-A, g-B, and g-C were 2.75, 3.67, and 2.26 Å (Figure 2A), respectively. 49 To understand the stability of peptides, RMSF and RMSD were analyzed in which fluctuations and deviations in terms of its residue and backbone conformations play an important role.…”
Section: Dynamic Analysis For Structural Stability and Functionalitymentioning
confidence: 99%